Modeling sequential R&D investments: A binomial compound option approach - Bastian Hauschild; Daniel Reimsbach (Business Research, 2015)
In this paper, we propose a binomial approach to modeling sequential R&D investments. More specifically, we present a compound real options approach, simplifying the existing valuation methodology. Based upon the same set of assumptions as prior models, we show that the number of computational steps for valuing any compound option can be reduced to a single step. We demonstrate the applicability of our approach using the real-world example of valuing a new drug application. Overall, our work provides a heuristic framework for fostering the adoption of binomial compound option valuation techniques in R&D management.
Keywords: O32; G11; 650; Research and development; Real options; Compound options; Resource allocation; Binomial model